Strategi pelestarian naskah kuno di Dinas Perpustakaan dan Kearsipan Provinsi Jawa Timur - Pramana, Wahyu Dian (Daluang: Journal of Library and Information Science, 2022)
Background. The implementation of preservation at The Library and Archives of East Java Province is less than optimal. This study aims to determine the strategies and efforts to develop the preservation of library materials at the Office of the Library and Archives of East Java Province, especially in the preservation of ancient manuscripts that are threatened with damage or loss due to physical damage.Methodology. This research is a descriptive research method with a quantitative and qualitative approach. The selection of informants in this study used the entire population of librarians in the field of preservation.Results and discussion. The results of this study show that the IFAS matrix shows that the strength and weakness factors have a total score of 2.28. Because the total score is above 0.73 it means that it identifies a strong internal position, where this strength has good strengths in terms of product. Furthermore, the EFAS matrix shows that the opportunity factor with a value of 0.68 and the threat has a value of 1.17. The total score between opportunities and threats is 1.85, with this identifying that responded that it was known after using strengths with SO opportunities and strategies.Conclusions. The right development strategy is SO and WO. SO strategies include improving the quality of deposit services, ancient manuscript services, and adding information repackaging services. And the WO strategy includes conducting conservation training for librarians, recruiting expert librarians with preservation qualifications, recruiting philologists, procuring preservation equipment, constructing standard preservation rooms or buildings.